2021
DOI: 10.1016/j.rmed.2021.106464
|View full text |Cite
|
Sign up to set email alerts
|

Pneumothorax in critically ill patients with COVID-19 infection: Incidence, clinical characteristics and outcomes in a case control multicenter study

Abstract: Background The clinical features and outcomes of mechanically ventilated patients with COVID-19 infection who develop a pneumothorax has not been rigorously described or compared to those who do not develop a pneumothorax. Purpose To determine the incidence, clinical characteristics, and outcomes of critically ill patients with COVID-19 infection who developed pneumothorax. In addition, we compared the clinical characteristics and outcomes of mechanically ventilated pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
59
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 25 publications
11
59
4
Order By: Relevance
“…
We read with great interest the article by Chopra et al recently published on Respiratory Medicine [1].In their multicenter study, the Authors present incidence, clinical characteristics and outcome of pneumothorax in critically ill patients with coronavirus disease 2019 . They found that pneumothorax rate among invasively ventilated COVID-19 patients is 80/594 (13 %), and mortality rate for patients who developed pneumothorax is 50/80 (62 %).
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
We read with great interest the article by Chopra et al recently published on Respiratory Medicine [1].In their multicenter study, the Authors present incidence, clinical characteristics and outcome of pneumothorax in critically ill patients with coronavirus disease 2019 . They found that pneumothorax rate among invasively ventilated COVID-19 patients is 80/594 (13 %), and mortality rate for patients who developed pneumothorax is 50/80 (62 %).
…”
mentioning
confidence: 99%
“…We read with great interest the article by Chopra et al recently published on Respiratory Medicine [1].…”
mentioning
confidence: 99%
“…Wang, in a series of 248 COVID-19 cases, reported that 2% of patients presented pneumothorax, which increased to 80% when ARDS was present; therefore, in that series, 80% of patients died [ 71 ]. The presence of pneumothorax with COVID-19 was diagnosed in 92% of patients who underwent invasive mechanical ventilation and in 13.72% of those who presented ARDS [ 78 ]; as well as in a multicenter retrospective analysis of all adult critically ill patients with COVID-19 infection, the overall incidence of pneumothorax in mechanically ventilated patients with COVID-19 infection was 13% [ 81 ]. In a retrospective study in China, pneumothorax occurred in 1% of patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have linked this association to the high levels of mechanical ventilation used in patients with severe COVID-19 disease. Patients with COVID-19 have a significantly elevated risk of pneumomediastinum and pneumothorax; the incidence of pneumothorax in mechanically ventilated patients with COVID-19 has been estimated to be 13% [6]. However, an analysis that compared cohorts of COVID-19 patients with non-COVID-19 patients on ventilation showed that patients with COVID-19 have a significantly higher incidence of pneumomediastinum compared to other ventilated patients with acute respiratory distress syndrome (13.6% vs. 1.9%), suggesting that coronavirus infection may have a causal role [7].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increased medical concern caused by a diagnosis of pneumomediastinum associated with COVID-19 pneumonitis, most cases can be managed conservatively with a good outcome and gradual resorption of air back into tissues [9]. However, further investigations may be warranted to rule out pneumothorax in these patients, which is clearly associated with worse outcomes [6].…”
Section: Discussionmentioning
confidence: 99%